Regulation of DNA duplication by the mTOR signaling pathway. Issue 8 (18th April 2021) - He, Zhengfu; Houghton, Peter J.; Williams, Terence M.; Shen, Changxian
ABSTRACT: Accurate and complete DNA replication and separation are essential for genetic information inheritance and organism maintenance. Errors in DNA duplication are the main source of genetic instability. Understanding DNA duplication regulation is the key to elucidate the mechanisms and find treatment strategies for human genetic disorders, especially cancer. The mechanistic target of rapamycin (mTOR) is a central regulator of cell growth and proliferation by integrating and processing extracellular and intracellular signals to monitor the well-being of cell physiology. mTOR signaling dysregulation is associated with many human diseases including cancer and diabetes. Emerging evidence has demonstrated that mTOR signaling plays a key role in DNA duplication. We herein review the current knowledge of mTOR signaling in the regulation of DNA replication origin licensing, replication fork progression, and stabilization.